Biomarkers of oxidative stress in Biomphalaria alexandrina snails for assessing the effects of certain inorganic fertilisers. (2nd October 2017) - El-Deeb, Fatma A.A.; Marie, Mohamed-Assem S.; Hasheesh, Wafaa S.; Hussein, Rehab M. A.; Sayed, Sara S. M.
ABSTRACT: Freshwater snails are often used to monitor aquatic pollution. The present study aims to use Biomphalaria alexandrina snails as bio-indicators for three types of NPK fertilisers (high nitrogen, high phosphorus and balanced). Data showed that high phosphorus and high nitrogen fertilisers have a negative impact on the growth rate of juvenile snails. Such observations were supported by determining antioxidant parameters in the digestive gland. Results indicated a significant increase in the catalase activity of snails that were exposed to ½ LC50 concentrations of balanced and high phosphorus fertilisers. Meanwhile, the glutathione S-transferase, glutathione peroxidase and reduced glutathione parameters showed varying results representing an increase or decrease in the activities of all treated groups after both the first and second weeks, according to the type of fertiliser the snails were exposed to.